Effects of genotype × environment interaction on eating and cooking quality of indica rice - BAO Jin-song; XIA Ying-wu (浙江大学学报. 农业与生命科学版, 2000)
The main genetic effects and genotype × environment interaction effects of endosperm, cytoplasm and maternal plants on eating and cooking quality of indica rice were analyzed in this paper. The results indicated that the amylose content and gelatinization temperature were controlled by the main genetic effects as well as by genotype × environment interaction effects, while gel consistency was mainly controlled by genotype × environment interaction effects. The heritabilities for three traits were high so selections for eating and cooking quality at the early generations could be effective. To predict genetic effects of parents and contrast their genetic effects showed that the parents with high amylose content were unfavorable for eating and cooking quality improvement. Prediction of heterosis for the F2 seeds revealed that seed-direct dominance effects might make the eating and cooking quality of the F2 seeds much poorer.